Equilibrium Selection in Cheap Talk Games: ACDC rocks when Other Criteria remain silent - Adrian de Groot Ruiz; Theo Offerman; Sander Onderstal (Tinbergen Institute, 2011)
Currently no refinement exists that successfully selects equilibria across a wider range of Cheap Talk games. We propose a generalization of refinements based on credible deviations, such as neologism proofness and announcement proofness. According to our Average Credible Deviation Criterion (ACDC), the stability of an equilibrium is determined by the frequency and the size of credible deviations. In our experiment, we find support for the relevance of credible deviations. In addition, we find support for ACDC in settings where other criteria remain silent. ACDC also explains results from previous experiments.
Keywords: C72; C92; D82; D83; 330; cheap talk; neologism proofness; announcement proofness; credible deviation; ACDC; experiment; Asymmetrische Information; Dynamisches Spiel; Nichtkooperatives Spiel; Theorie